Relationship of Migraine and Body Mass Index (BMI) (Journal of Enam Medical College, 2016)
Background: Migraine is an important cause of headache and headache-related disabilities. It increases loss of working time, causes inability to carry out daily activities and disruption of family and social life. The pathophysiology of migraine is still poorly understood. On the other hand, the prevalence of obesity is constantly increasing worldwide. The consequence of overweight and obesity includes increased risk of diabetes mellitus, dyslipidemia, hypertension, cardiovascular disease and cancer.Objectives: This study was performed to assess the relationship between BMI and migraine by finding out the relationship between migraine frequency and duration in different BMI groups, comparing the socio-demographic variables in migraine and non-migraine patients and to find out the migraine related co-morbidities.Materials and Methods: This observational case-control study was conducted on 100 subjects aged 1250 years in the Neurology Outpatient Department, Mymensingh Medical College Hospital, Mymensingh in the period of January 2011 to December 2012. Out of total subjects fifty migraine patients were selected as cases and fifty nonmigraineurs as controls. Subjects were then categorized in three groups based on BMI: 25. Collected data were compiled and appropriate analyses were done by using computer based software, Statistical Package for Social Sciences (SPSS) version 16.0. For statistical analysis one way ANOVA tests were done for comparing means of quantitative data and Chi-square tests were done for qualitative data. A p value 95%) of the study subjects were between 10 and 35 years of age. Mean age of case group was found 25.55 ± 5.87 and that of control was 25.53 ± 4.22 years. Case group contained 10 (20%) males and 40 (80%) females whereas control group had 14 (28%) males and 36 (72%) females. Number of female cases and controls were higher than that of male. In control group 30 (60%) were unmarried and 20 (40%) were married. There was no significant difference in the financial condition between case and control groups. Students and housewives occupied the largest number of study subjects who were unemployed. Regarding residence, rural and urban patients were equal in case group and in control group 29 (58%) were urban and 21 (42%) rural. Mean duration of headache was 8.9 ± 7.5, 5.8 ± 6.7, 9.6 ± 14.3 years in different BMI groups (25 respectively) in case group and 4.6 ± 5.3, 4.4 ± 3.4, 3.4 ± 1.4 years in control group respectively. There was significant difference in quality of headache. In migrainous group 58.6% in BMI 25 noted their headache as throbbing, in contrast most of the nonmigrainous described them as dull in nature. Mean frequency of headache per month was significantly higher in migraine group compared to non-migraine group (p=0.02). Regarding associated symptoms, nausea, vomiting, photophobia and phonophobia were observed significantly higher in migraine patients in BMI